Erratum to: Detecting long-lived multi-charged particles in neutrino mass models with MoEDAL - Martin Hirsch; Rafał Masełek; Kazuki Sakurai (European Physical Journal C: Particles and Fields, 2022)
A Correction to this paper has been published: 10.1140/epjc/s10052-021-09507-9